Implementation of Video Animation Media for Ablution Materials to Improve Student Understanding - Rizqi Citra Lestari; Eni Fariyatul Fahyuni (Institut Agama Islam An-Nawawi Purworejo, 2023)
This research is motivated by the use of learning media on the material of ablution' is not optimal, thus causing students' incomprehension of the sequence of ablution which is generally experienced by students. Therefore, researchers tried to use learning media in the form of animated videos, which have the advantage of visualising the steps of wudhu' that are interesting and interactive, and are able to present moving objects accompanied by sound. The purpose of this study is to assess whether the use of animated video media can improve students' understanding of the correct sequence in carrying out the procedure of wudhu' at MI Muhammadiyah 2 Kedungbanteng. This study used an experimental method with an independent sample t-test, the samples in this study were class 1 as the experimental class and class 2 as the control class, where the number of students from both classes was 40 with the number of each class as many as 20 children. The results showed that the Sig (2-tailed) value was 0.010 < 0.05, so H0 was rejected and Ha was accepted. This shows that learning using animated videos has a significant effect on students' understanding of ablution procedures at MI Muhammadiyah 2 Kedungbanteng.